2015
DOI: 10.1002/2014jd022246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating convective parameterization closures using cloud‐resolving model simulation of tropical deep convection

Abstract: Closure is an important component of a mass flux-based convective parameterization scheme, and it determines the amount of convection with the aid of a large-scale variable (closure variable) that is sensitive to convection. In this study, we have evaluated and quantified the relationship between commonly used closure variables and convection for a range of global climate model (GCM) horizontal resolutions, taking convective precipitation and mass flux at 600 hPa as measures for deep convection. We have used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 62 publications
2
29
2
Order By: Relevance
“…Additional attempts were also considered to segregate the GoAmazon2014/5 data set into ensemble mean profiles according to the upper and lower standard deviation values for CAPE, CIN, and low‐level RH. One alternative was to explore basic correlations between the thermodynamic quantities of interest and velocity or mass flux profile values (as in other conventional GCM efforts) [e.g., Suhas and Zhang , ]. Unfortunately, those breakdowns typically reflected insufficient sample populations or required larger increments of the thermodynamic quantities (e.g., CAPE bins in 1000 J kg −1 increments) to generate representative profiles with confidence (peaked distributions as in Figure ).…”
Section: Interpretation Of Amazon Ensemble Profile Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional attempts were also considered to segregate the GoAmazon2014/5 data set into ensemble mean profiles according to the upper and lower standard deviation values for CAPE, CIN, and low‐level RH. One alternative was to explore basic correlations between the thermodynamic quantities of interest and velocity or mass flux profile values (as in other conventional GCM efforts) [e.g., Suhas and Zhang , ]. Unfortunately, those breakdowns typically reflected insufficient sample populations or required larger increments of the thermodynamic quantities (e.g., CAPE bins in 1000 J kg −1 increments) to generate representative profiles with confidence (peaked distributions as in Figure ).…”
Section: Interpretation Of Amazon Ensemble Profile Behaviorsmentioning
confidence: 99%
“…As in that study, we document the vertical structure of convective mass flux, the relative role of convective area fraction and vertical velocity on mass flux, and the sensitivity of vertical velocity and mass flux profiles to changes in thermodynamics conditions. Efforts along these lines may act as a pure observational complement to help anchor other recent GCM convective parameterization environmental forcing and closure studies [e.g., Suhas and Zhang , ].…”
Section: Introductionmentioning
confidence: 99%
“…divided by 32). Following the definition in Suhas and Zhang (2015), a CSRM column is categorized as convective if at any level the Geosci. Model Dev.…”
Section: Convective Precipitation Definitionmentioning
confidence: 99%
“…The examination of the relationship between convective activity and large-scale fields can provide valuable information for evaluating and improving convective parameterization. Suhas and Zhang examined several large-scale variables used in convective parameterization closures using a cloud-resolving model (CRM) simulation of unorganized tropical convection by Zeng et al [19]. They found that moisture convergence has the best relationship with convection among all closure variables they examined.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an earlier study [20] found that the quasi-equilibrium closure broke down when the domain size was too small to provide an adequate sampling of the cloud field or under rapidly changing large-scale forcing. In addition, Suhas and Zhang [19] was for unorganized convection. Do their conclusions apply to organized convection such as mesoscale convective systems?…”
Section: Introductionmentioning
confidence: 99%